The use of rat liver nucleoplasm for the characterization of heterogeneous nuclear ribonucleic acid synthesis in vitro. - Beebee, T J (1978)
1. A nucleoplasmic fraction rich in endogenous RNA polymerase II activity was isolated from rat liver nuclei and conditions were determined under which elongation of RNA molecules initiated in vivo continued at maximal rates in vitro. 2. Elongation rates in vitro were calculated to be about 0.25 nucleotide/s and there were about 7 X 10(3) RNA molecules in the process of being elongated by form-II RNA polymerase per original nucleus. 3. Evidence was obtained suggesting that transcription-dependent release of RNA polymerase II molecules from the template occurred during the incubations in vitro. 4. The nascent RNA was tightly associated with protein and banded as ribonucleoprotein in caesium salt gradients. 5. RNA molecules labelled in vitro were up to 13000 nucleotides in length, but consisted of long unlabelled chains transcribed in vivo with only short labelled sequences added in vitro, and without significant polyadenylation. 6. Hybridization of transcripts in the presence of a vast excess of DNA demonstrated that both form-II RNA polymerase and another enzyme, resistant to low alpha-amanitin concentrations, were synthesizing RNA molecules complementary to both reiterated and unique DNA sequences in the genome.